UPAYA PENINGKATAN MOTIVASI DAN AKTIVITAS BELAJAR BIOLOGI SISWA MELALUI STRATEGI THINK TALK WRITE (TTW) SISWA KELAS X1 SMA NEGERI 1 KAMPAR KIRI TAHUN AJARAN 2009/2010 - Arnentis '; Darmawati '; Idel Fitri Mulyani (Program Studi Pendidikan Biologi, 2011)
The aim of this research are to improve motivation and students activity of learning class X1 SMAN 1 Kampar Kiri by using think talk write strategy. This class action research has been done on March till May 2010. Subject of the research are 32 class X1 student of SMAN 1 Kampar Kiri with 14 males and 18 females. Parameters of the research are motivation with several indicators namely: interest, relevancy, hope, result, and students activity. The average score means of student motivation before research treatment is 2,93 (medium category), after cycle 1 get increase to 3,48 (medium category) with increase presentation 18,15%%, cycle 2 can make increase till reach means 4,92 (high category) with increase presentation 34,38%. The average student activity increased from cycle 1 is 65.6% and the cycle 2 is 83.2%. Using think talk write strategy can improve motivation and students activity of learning class X1 SMAN 1 Kampar Kiri.